Examining the intersectionality among teacher race/ethnicity, school context, and risk for occupational stress - Fitchett, Paul G.; Dillard, Jendayi; McCarthy, Christopher J.; Lambert, Richard G.; Mosley, Kristen (Education Policy Analysis Archives, 2020)
Combining secondary data from the National Center for Education Statistics National Teacher Principal Survey (NTPS) and Common Core of Data (CCD), this exploratory study examined the distribution of teacher race/ethnicity across the race/ethnicity of the schools in which they work and the extent that teacher and school race/ethnicity was associated with occupational stress. Findings indicate that teachers are more likely to work in schools with higher concentrations of students who match their own race/ethnicity. Both teacher and school race/ethnicity were unique predictors of a teacher being classified as at-risk for stress. Additional analyses suggested that teachers’ reported race/ethnicity significantly moderated the school effect association with stress risk. These findings have policy implications for how school workplace surveys are used as well as staffing and professional development considerations.